Structural Studies of the ATPase from the Type II Secretion System - Lu, Yiching (My University, 2014)
The type II secretion system (T2SS) in Gram-negative bacteria is a multi-protein machinery that spans both the inner and the outer membranes. The T2SS in Vibrio cholerae, secretes folded proteins including the major virulence factor, cholera toxin, from the periplasm across the outer membrane into the intestinal tract of the host. The T2SS contains 12-15 different proteins, with many of them present in multiple copies. This system can be divided into three major sub-assemblies: the outer membrane complex, the pseudopilus, and the inner membrane complex. The inner membrane complex contains the only ATPase GspE of the T2SS, and is thought to provide the energy for T2SS assembly or secretion. GspE belongs to the Type II/IV secretion ATPase family and has three domains, N1E, N2E and CTE. GspE is tightly associated with the inner membrane complex through its N1E interacting with the cytoplasmic domain of the inner membrane protein GspL (cyto-GspL). Although numerous members of the Type II/IV secretion ATPases have been characterized or crystallized as hexamers, the N1E-truncated GspE crystallized as a 61-helical filament. To this date, the oligomeric state of GspE remains unclear. Here, we unravel the crystal structure of the full-length GspE in complex with cyto-GspL from Vibrio vulnificus in the presence of a non-hydrolysable ATP analogue AMPPNP. The structure revealed a novel mutual orientation of N2E and CTE, cyto-GspL rods that extend throughout the crystal, and unexpected interactions of cyto-GspL with AMPPNP and CTE. The GspE in complex with cyto-GspL structure shows no evidence of GspE multimers, therefore, an "assistant hexamer" Hcp1 was fused to GspE for facilitating GspE hexamerization. The N1E-truncated Vibrio cholerae GspE fused to Hcp1 showed a ~20-fold increase in ATPase activity compared to the monomeric form, and crystallized into two different hexamers: a quasi-C6 regular hexamer and an elongated C2 hexamer. Small-angle X-ray scattering studies of the fusion supports the hexameric forms observed in the structures are present in solution, but several conformations are in equilibrium in solution. Based on the analysis of domain arrangements and comparison with homologs from the Type II/IV secretion ATPases, GspE shows considerable conformational flexibility and likely undergoes several different conformations during the secretion process.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Biochemistry; biological chemistry